Activity of Catalytic Ceramic Papers to Remove Soot Particles—A Study of Different Types of Soot - Leonardi, Sabrina Antonela (2022)
Diesel soot particles are of concern for both the environment and health. To catalytically remove them, it is important to know their structure and composition. There is little described in the literature on how catalysts favor the combustion of different soot fractions. In this work, programmed temperature oxidation (TPO) experiments were carried out using Co,Ce or Co,Ba,K catalysts supported on ceramic papers. Soot particles were obtained by burning diesel fuel in a vessel (LabSoot) or by filtering exhaust gases from a turbo diesel engine in a DPF filter (BenchSoot), and compared with a commercial diesel soot: Printex U. Various characterization techniques were useful to relate the characteristics of both the soot particles and the catalysts with the TPO results. The maximum catalytic soot burn rate (TM) temperatures were in the range of diesel exhaust temperatures that would facilitate in-situ regeneration of the DPF. The Co,Ba,K catalyst showed a higher catalytic effect in LabSoot, as the latter exhibited the largest primary particles and the higher order of graphene layers, for which the potassium-containing catalyst improves the contact between soot and catalyst and favors the combustion of soot, while the Co,Ce catalyst preferentially enhanced the combustion of commercial soot by supplying active oxygen.